IMPROVING THE PRACTICE OF PUBLIC PLACEMENT OF SECURITIES - Berdiqulova Manzura Raxmonqulovna (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, we studied the stock market in Uzbekistan. To date, the transition of the economy to the market economy and the formation of the securities market required the restoration of the types of securities and the creation of new types. In turn, the study of all the opportunities offered by this market also created the need to analyze modern methods of attracting capital in this market.